Chinese antiquities an introduction to the art market - Wang, Audrey (Handbooks in international art business., 2012)
Chinese Antiquities: An Introduction to the Art Market provides an essential guide to the growing market for Chinese antiquities, encompassing all sectors of the market, from Classical Chinese paintings and calligraphy to ceramics, jade, bronze and ritual sculpture.